2021
DOI: 10.1002/app.50453
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale simulation on dynamic friction behavior of cylinder sealing rings under hydrothermal aging

Abstract: The friction behavior of cylinder seal greatly affects the dynamic position accuracy of the cylinder execution terminal under hydrothermal aging. So, the hydrothermal aging test, friction test, tensile and compression test, topography analysis and infrared spectroscopy analysis, and multiscale simulation were carried out for studying the effect of the hydrothermal aging on the friction performance of cylinder seal. It was found that when the aging temperature increases from 40 to 80°C, the dynamic friction for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Azzi et al [7] studied the influence of different sealing elements and operating parameters on the frictional force of sealing elements. Luo et al [8] conducted a simulation of the frictional behavior of the cylinder seal, combining the analysis results with the experimental results to reveal the dynamic changes of the seal caused by friction. Yakovlev [9] provided a detailed experimental setup to study the wear of lip seals in frictional contact with rotating shafts.…”
Section: Introductionmentioning
confidence: 99%
“…Azzi et al [7] studied the influence of different sealing elements and operating parameters on the frictional force of sealing elements. Luo et al [8] conducted a simulation of the frictional behavior of the cylinder seal, combining the analysis results with the experimental results to reveal the dynamic changes of the seal caused by friction. Yakovlev [9] provided a detailed experimental setup to study the wear of lip seals in frictional contact with rotating shafts.…”
Section: Introductionmentioning
confidence: 99%
“…He et al [ 33 ] investigated the tribological performance of CeO 2 blended rubber after aging and showed that the increase in crosslink density at the beginning of thermal aging could effectively improve its tribological performance. Luo et al [ 34 ] found that the friction and contact pressure of NBR seals increased with the increase in temperature during hydrothermal aging.…”
Section: Introductionmentioning
confidence: 99%
“…Sang et al [14] employed a method of measuring the axial rod friction in a triaxial apparatus by combining a numerical method with an experimental method. Luo et al [15] conducted a multi-scale simulation analysis on the friction behavior of cylinder seal rings in a cylinder, and by combining the analysis with the experimental results, revealed dynamic changes in the seal ring caused by friction. Kaushal et al [16] studied the influence of geometry on the sealing characteristics of V-seal and provided a structural optimization design.…”
Section: Introductionmentioning
confidence: 99%